A humidity-enhanced silicon-based semiconductor tribovoltaic direct-current nanogenerator. Issue 47 (18th November 2022) - Wang, Zhaozheng; Gong, Likun; Dong, Sicheng; Fan, Beibei; Feng, Yuan; Zhang, Zhi; Zhang, Chi
Abstract : A humidity-enhanced tribovoltaic nanogenerator achieves a milestone of charge density, which is 4 times that of the previously reported triboelectric nanogenerator in high-humidity environments. Abstract : The triboelectric nanogenerator (TENG) which could convert mechanical energy into electrical energy has attracted worldwide attention in energy harvesting and the Internet of Things (IoTs). However, the extreme performance degradation in high-humidity environments is a big challenge. Here, a humidity-enhanced silicon-based semiconductor tribovoltaic direct-current nanogenerator (TVNG) is reported. The transferred charge and peak power in high-humidity environments (RH 90%) can reach 12.6 mC m −2 and 1.6 mW m −2, which are nearly 88 times and 100 times of those in low humidity (RH 30%), respectively. In particular, the TVNG achieves a milestone of transferred charge density, which is 4 times that of the previously reported traditional polymer TENG in high-humidity environments (RH 90%). The mechanism of performance improvement for the TVNG in high-humidity environments is analyzed in detail, which is attributed to the coupling effect of the enhanced surface states and reduced contact resistance. This research provides an effective approach to promote the output performance of a TVNG, which demonstrates the great application potential of the semiconductor tribovoltaic effect in high-humidity environmental energy harvesting such as oceans, rains, etc.